Stereoselective cathodic synthesis of 8-substituted (1R,3R,4S)-menthylamines - Edinger, Carolin; Kulisch, Jörn; Waldvogel, Siegfried R. (Beilstein Journal of Organic Chemistry, 2015)
The electrochemical generation of menthylamines from the corresponding menthone oximes equipped with an additional substituent in position 8 is described. Due to 1,3-diaxial interactions a pronounced diastereoselectivity for the menthylamines is found.
Keywords: cathodic reduction; chiral amines; electrosynthesis; menthylamines; oximes

Chiral auxiliaries and ligands in asymmetric synthesis - Seyden-Penne, J. (Wiley Inter-Science, 1995)

(untitled) - France, S.; Guerin, D. J.; Miller, S. J.; Lectka, T. (Chem. Rev., 2003)

(untitled) - Nugent, T. C.; El-Shazly, M. (Adv. Synth. Catal., 2010)

(untitled) - Newman, D. J.; Cragg, G. M.; Snader, K. M. (J. Nat. Prod., 2003)

(untitled) - Fiori, K. W.; Du Bois, J. (J. Am. Chem. Soc., 2007)

(untitled) - Li, Z.; Capretto, D. A.; Rahaman, R.; He, C. (Angew. Chem., 2007)
Angew. Chem., Int. Ed. 2007, 46, 5184–5186. doi:10.1002/anie.200700760

(untitled) - Milczek, E.; Boudet, N.; Blakey, S. (Angew. Chem., 2008)
Angew. Chem., Int. Ed. 2008, 47, 6825–6828. doi:10.1002/anie.200801445

(untitled) - Liang, C.; Collet, F.; Robert-Peillard, F.; Müller, P.; Dodd, R. H.; Dauban, P. (J. Am. Chem. Soc., 2008)

(untitled) - Gribkov, D. V.; Hultzsch, K. C.; Hampel, F. (J. Am. Chem. Soc., 2006)

(untitled) - LaLonde, R. L.; Sherry, B. D.; Kang, E. J.; Toste, F. D. (J. Am. Chem. Soc., 2007)

(untitled) - Zhang, Z.; Bender, C. F.; Widenhoefer, R. A. (J. Am. Chem. Soc., 2007)

(untitled) - Nishina, N.; Yamamoto, Y. (Angew. Chem., 2006)
Angew. Chem., Int. Ed. 2006, 45, 3314–3317. doi:10.1002/anie.200600331

(untitled) - Wood, M. C.; Leitch, D. C.; Yeung, C. S.; Kozak, J. A.; Schafer, L. L. (Angew. Chem., 2007)
Angew. Chem. Int. Ed. 2007, 47, 354–358. doi:10.1002/anie.200603017

(untitled) - Blaser, H. U. (Chem. Rev., 1992)

(untitled) - Kauffman, G. S.; Harris, G. D.; Dorow, R. L.; Stone, B. R. P.; Parsons, R. L., Jr; Pesti, J. A.; Magnus, N. A.; Fortunak, J. M.; Confalone, P. N.; Nugent, W. A. (Org. Lett., 2000)

(untitled) - Chrisman, W.; Camara, J. N.; Marcellini, K.; Singaram, B.; Goralski, C. T.; Hasha, D. L.; Rudolf, P. R.; Nicholson, L. W.; Borodychuk, K. K. (Tetrahedron Lett., 2001)

(untitled) - Goralski, C. T.; Chrisman, W.; Hasha, D. L.; Nicholson, L. W.; Rudolf, P. R.; Zakett, D.; Singaram, B. (Tetrahedron: Asymmetry, 1997)

(untitled) - Masui, M.; Shioiri, T. (Tetrahedron, 1995)

(untitled) - Kitamura, M.; Suga, S.; Kawai, K.; Noyori, R. (J. Am. Chem. Soc., 1986)

(untitled) - Rishton, G. M.; Retz, D. M.; Tempest, P. A.; Novotny, J.; Kahn, S.; Treanor, J. J. S.; Lile, J. D.; Citron, M. (J. Med. Chem., 2000)

(untitled) - Periasamy, M.; Devasagayaraj, A.; Satyanarayana, N.; Narayana, C. (Synth. Commun., 1989)

(untitled) - Yamaguchi, H.; Minoura, Y. (J. Polym. Sci., Part A-1: Polym. Chem., 1970)

(untitled) - Boyle, P. H. (Q. Rev., Chem. Soc., 1971)

(untitled) - Malkowsky, I.; Nieger, M.; Kataeva, O.; Waldvogel, S. R. (Synthesis, 2007)

(untitled) - Wilkerson, W. W.; Galbraith, W.; DeLucca, I.; Harris, R. R. (Bioorg. Med. Chem. Lett., 1993)

(untitled) - Kulisch, J.; Nieger, M.; Stecker, F.; Fischer, A.; Waldvogel, S. R. (Angew. Chem., 2011)
Angew. Chem., Int. Ed. 2011, 50, 5564–5567. doi:10.1002/anie.201101330

(untitled) - Corey, E. J.; Gross, A. W. (J. Org. Chem., 1985)

(untitled) - Oertling, H.; Reckziegel, A.; Surburg, H.; Bertram, H.-J. (Chem. Rev., 2007)

(untitled) - Schopohl, M. C.; Siering, C.; Kataeva, O.; Waldvogel, S. R. (Angew. Chem., 2003)
Angew. Chem., Int. Ed. 2003, 42, 2620–2623. doi:10.1002/anie.200351102

(untitled) - Siering, C.; Grimme, S.; Waldvogel, S. R. (Chem. – Eur. J., 2005)

(untitled) - Schopohl, M. C.; Faust, A.; Mirk, D.; Fröhlich, R.; Kataeva, O.; Waldvogel, S. R. (Eur. J. Org. Chem., 2005)

(untitled) - Bomkamp, M.; Siering, C.; Landrock, K.; Stephan, H.; Fröhlich, R.; Waldvogel, S. R. (Chem. – Eur. J., 2007)

(untitled) - Orghici, R.; Willer, U.; Gierszewska, M.; Waldvogel, S. R.; Schade, W. (Appl. Phys. B, 2008)

(untitled) - Börner, S.; Orghici, R.; Waldvogel, S. R.; Willer, U.; Schade, W. (Appl. Opt., 2009)

(untitled) - Arlt, D.; Bömer, B.; Grosser, R.; Lange, W. (Angew. Chem., 1991)
Angew. Chem., Int. Ed. 1991, 50, 1662–1664. doi:10.1002/anie.199116621

Ger. Pat. Appl. - Schwartz, U.; Großer, R.; Piejko, K.-E.; Arlt, D. (Optisch aktive (Meth)-acrylamide, Polymere daraus, Verfahren zu ihrer Herstellung und ihre Verwendung zur Racematspaltung, 1987)
Chem. Abstr. 1987, 107, 40614.

Ger. Pat. Appl. - Bömer, B.; Großer, R.; Lange, W.; Zweering, U.; Köhler, B.; Sirges, W.; Grosse-Bley, M. (Chirale stationäre Phasen für die chromatographische Trennung von optischen Isomeren, 1997)
Chem. Astr. 1997, 127, 96037.

Ger. Pat. Appl. - Lange, W.; Großer, R.; Michel, S.; Bömer, B.; Zweering, U. (Chromatographische Enantiomerentrennung von Lactonen, 1998)
Chem. Abstr. 1998, 129, 290016.

(untitled) - Wallach, O. (Ber. Dtsch. Chem. Ges., 1891)

(untitled) - Kozlov, N. G.; Pekhk, T. I.; Vyalimyaé, T. K. (Chem. Nat. Compd., 1981)

(untitled) - Feltkamp, H.; Koch, F.; Thanh, T. N. (Justus Liebigs Ann. Chem., 1967)

(untitled) - Kozlov, N. G. (Chem. Nat. Compd., 1982)

(untitled) - Welschoff, N.; Waldvogel, S. R. (Synthesis, 2010)

(untitled) - Schmitt, M.; Schollmeyer, D.; Waldvogel, S. R. (Eur. J. Org. Chem., 2014)

(untitled) - Schopohl, M. C.; Bergander, K.; Kataeva, O.; Fröhlich, R.; Waldvogel, S. R. (Synthesis, 2003)

(untitled) - Edinger, C.; Waldvogel, S. R. (Eur. J. Org. Chem., 2014)

(untitled) - Edinger, C.; Grimaudo, V.; Broekmann, P.; Waldvogel, S. R. (ChemElectroChem, 2014)